Mining Businesses of C Exvacation On The Real Regional Income In Improving Economic Security - Zainal Abidin (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2018)
This research is conducted because of the fact that mining business of quarry mining C can increase the original income in order to strengthen national economic resilience. The objective of this research is to analyze the  quarry mining C business in improving national economic resilience. This research uses qualitative method. Data obtained through interviews to informants and direct observation in the field, as well as literature study. The result of the research shows that the quarry mining C business  in Pankajene dan Kepulauan (Pangkep) can contribute to the original income of the region because of the effective targets applied by the local government of Pangkep Regency in relation to the retribution of each mining miner C, the effectiveness of retribution is encouraged by the policy Issued by the local government of Pangkep district  in the form of a regional regulation . This is indicated by the awareness of the quarry mining C business actors which is positively related to the smoothness of retribution payments to increase the original income in the framework of national economic resilience.Keywords: Quarry Mining C; Retribution; Increasing original income; National Economic Resilience.